The Case of George M'Intosh, Esquire, a member of the late Council and Convention of the state of Georgia : with the proceedings thereon in the Hon. the Assembly and Council of that state (Printed [by Lancaster & Mumford?], 1777)
This case details accusations against M'Intosh for being a loyalist in sending his rice crop to British ships and of breaking the law prohibiting trade with the British. Arrested, with much of his estate was seized by the head of Georgia, without consultation of his Council. George claimed innocence, claiming he was deceived by his partners who were Tories.A defense of M'Intosh against charges of loyalist sympathies.